Two Sciatic Type Syndromes that Resemble Disc Prolapse - Swee, Brian John (International Journal of Orthopedics and Rehabilitation, 2018)
Background: The recognition of distinctive forms of common low back pain remains a problem. The aim of this study was to define two sciatic type syndromes, which mimic lumbar disc protrusion, but do not exhibit nerve root compression. Methods: This is a revision of the original diagnostic classification, which had been produced by cluster analysis. By adopting the 9-subgroup rather than the 7-subgrouping solution, two seemingly useful sciatic type syndromes were revealed. These two extra syndromes are inspected alongside classical L5 and S1 prolapsed disc subgroups. These are compared in terms of 25 previously short listed clinical features that had been selected by discriminant analysis as best for describing low back pain in general. Results: One of the “new” sciatic type syndromes was seen in patients with a relatively young age of onset of their problems with mean 23.0 ± SD 8.7 years (overall it was 30.6 ± SD 14.1 years). On average it took 19.4 ± 11.0 years until this group were seen in our hospital rheumatology department based back pain clinic, though such patients would previously have seen other practitioners. The patients with the other new sciatic type syndrome had older age of onset (mean 51.5 ± SD 10.8 years) and were predominantly female (78%). Discussion: Our original study was conducted completely separately from, and in an era when McKenzie was evolving his mechanical diagnostic system. It is now suspected that his concept of “disc like syndromes that might not need surgery” might help explain the clinical relevance of our two additional sciaticaform subgroups. That these two syndromes had cladistically derived from a single previously combined syndrome which had been subsumed into an L5 disc like conglomerate perhaps explains why they can appear so similar clinically, and yet may need to be distinguished therapeutically and prognostically. Conclusions: These diagnostic revisions could hopefully improve clinical insight into non-specific low back pain. They help identify two sciatic type syndromes that appear similar to those with disc prolapse but do not demonstrate signs of nerve root compression. It remains to be seen whether these truly reflect any of the McKenzie entities, and if not, what they might actually mean.